A Nearly Exact Discretization Scheme for the FitzHugh–Nagumo Model - Kwessi, Eddy; Edwards, Lloyd J. (Differential equations and dynamical systems, 2024)
In this paper, we apply the nearly exact discretization schemes to propose a discrete model for the FitzHugh–Nagumo model. We show that the discrete model obtained preserves the dynamics and the known features of the continuous FitzHugh–Nagumo model. We do so by performing distance-based and probability-based similarity analysis. Additionally, a sensitivity analysis is also performed to analyze the most influential parameters of the discrete system.